2021
DOI: 10.3390/diagnostics11010122
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Radioembolization of Hepatocellular Carcinoma, Liver-Dominant Hepatic Colorectal Cancer Metastases, and Cholangiocarcinoma Using Yttrium90 Microspheres: Eight-Year Single-Center Real-Life Experience

Abstract: Liver tumors are common and may be unamenable to surgery or ablative treatments. Consequently, other treatments have been devised. To assess the safety and efficacy of transarterial radioembolization (TARE) with Yttrium-90 for hepatocellular carcinoma (HCC), liver-dominant hepatic colorectal cancer metastases (mCRC), and cholangiocarcinoma (CCA), performed according to current recommendations, we conducted a single-center retrospective study in 70 patients treated with TARE (HCC, n = 44; mCRC, n = 20; CCA, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The incidence of serious adverse events is relatively low and recovery can be achieved through drug withdrawal or hormone therapy. Research by the current authors has indicated that a combination of an ICI and an TKI resulted in an adverse event incidence of about 46.9%, most of which are below grade three (63).The incidence of grade three or four adverse events was 6.1% which is significantly lower than that of other treatment modalities (18,42,(44)(45)(46)(64)(65)(66). Adverse events are grouped in accordance with the National Cancer Institute Common Terminology Criteria for Adverse Events version 4.0 (53).…”
Section: A Combination Of An Ici and An Aad Offers Hope As A Conversi...mentioning
confidence: 82%
See 1 more Smart Citation
“…The incidence of serious adverse events is relatively low and recovery can be achieved through drug withdrawal or hormone therapy. Research by the current authors has indicated that a combination of an ICI and an TKI resulted in an adverse event incidence of about 46.9%, most of which are below grade three (63).The incidence of grade three or four adverse events was 6.1% which is significantly lower than that of other treatment modalities (18,42,(44)(45)(46)(64)(65)(66). Adverse events are grouped in accordance with the National Cancer Institute Common Terminology Criteria for Adverse Events version 4.0 (53).…”
Section: A Combination Of An Ici and An Aad Offers Hope As A Conversi...mentioning
confidence: 82%
“…Specific methods include associating liver partition and portal vein ligation for staged hepatectomy, ablation, TACE, HAIC, SBRT, CCRT, TARE, TKIs, ICIs, and multimodality treatment approaches (16,18,42,43). Conversion outcomes of various approaches are cited in Table 3 (16,18,42,(44)(45)(46). Despite controversies, mounting data have indicated that successful conversion treatment followed by subsequent surgery is achievable in the population of patients with advanced HCC (47).…”
Section: Current Status Of Conversion Therapy For Advanced Hccmentioning
confidence: 99%
“…Thus, numerous studies have demonstrated its therapeutic efficacy and safety [21,51]. Among its prominent applications is transarterial radioembolization for the treatment of primary and secondary liver cancers [52,53]. It takes advantage of the dual blood supply of the liver, which permits it to suppress the tumor feeding, while preserving the liver.…”
Section: Discussionmentioning
confidence: 99%
“…An amount of 1 mL of freshly prepared 90 Y-hinokitiol (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64) in Lipiodol phase was taken with a syringe and put into a 12-mL flat bottom glass vial, containing 10 mL of physiological serum (previously weighed), and the vial was closed. Activity in the vial was measured with the dose calibrator.…”
Section: Over Time Release In the Aqueous Phasementioning
confidence: 99%
“…Transarterial radioembolization with yttrium-90 (90Y) microspheres is a form of brachytherapy that uses the hepatic arterial supply to permanently implant 90Y in the target tumor through the injection of resin or glass microspheres [ 23 ].…”
Section: Vascular and Non-vascular Approachesmentioning
confidence: 99%